POLA RELASI BISNIS DAN POLITIK DI INDONESIA MASA REFORMASI: KASUS RENT SEEKING - Solihah, Ratnia (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
Patterns of business and political relations in the reform period is one form of transformation of the pattern of political and business relations of the New Order. This relation involving actors in the political and economical sector through the actions taken to share the resources of the state, where the practice of rent seeking is done openly in a democratic regime. Rent seeking in the reform period was transformed through regime change, from the authoritarian New Order regime to democratic regime in reform period. In the transformation process, rent seeking growing not only among economical and political / governmental actors at the central level but also extends to localactors. The shift in the relation of power from the center to the regions shifting the map of corruption that was once centralized and then spread to smaller level of area. Pattern of business and political relationships was transformed due to the reorganization of the business actors during the New Order to the current political situation to keep control of economic resources; The appearance of new businesses as new economic powers; and the presence of political/governmental actors still dominated by predatory power relations and clientelism.